2020
DOI: 10.1088/1742-6596/1566/1/012078
|View full text |Cite
|
Sign up to set email alerts
|

Information visualization of metacognitive skills during the software development process based on an adapted engineering design metacognitive questionnaire

Abstract: In software development, either alone or in a team, there are many aspects that determine the success in developing the software, including each developer’s skills. Studies show that the application of metacognition can increase the effectiveness and efficiency of software development. To measure a metacognition skill, there need to be a metacognition measurement tools. One example of this measurement method is adapted engineering design metacognitive questionnaire. However, the respondents feel that existing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Compared with the 3D plane IV, the 3D spatial IV can display better effects and images that are more in line with people's normal way of thinking. However, it has high requirements for the designers' professional skills and aesthetic sense, so people are more inclined to choose 2D plane IV methods [23,24].…”
Section: Bc Technology and IV Analysismentioning
confidence: 99%
“…Compared with the 3D plane IV, the 3D spatial IV can display better effects and images that are more in line with people's normal way of thinking. However, it has high requirements for the designers' professional skills and aesthetic sense, so people are more inclined to choose 2D plane IV methods [23,24].…”
Section: Bc Technology and IV Analysismentioning
confidence: 99%
“…The study findings showed that the agile students completed the task within a period of time. [ 27 ] The study done by Kroop reported that the students’ practical skills were improved in computer science students after learning agile methodology. [ 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…Especially in the pandemic situation of Covid-19, which is learning online as E-learning, students should have more self-dedication and concentration in programming courses because of its complexity and acquire the willingness of students to reach the goals needed from the university (Mbunge, Fashoto, & Olaomi, 2021). E-learning is a conventional method of educational process in the technology era which engages the lecturers and students in different sites apart from the classroom to conduct teaching activities (Adisurya, Santoso, Fadhilah, & Lawanto, 2020). Likely face-to-face classes, learning in distance via platform room channels, by utilizing electronic and software tools such as laptop and E-learning websites, also remains effective to facilitate both the learners, as said in (Adisurya et al, 2020), to adjust this environment and learn intensively, and the lecturers to deliver the material concisely.…”
Section: Introductionmentioning
confidence: 99%
“…E-learning is a conventional method of educational process in the technology era which engages the lecturers and students in different sites apart from the classroom to conduct teaching activities (Adisurya, Santoso, Fadhilah, & Lawanto, 2020). Likely face-to-face classes, learning in distance via platform room channels, by utilizing electronic and software tools such as laptop and E-learning websites, also remains effective to facilitate both the learners, as said in (Adisurya et al, 2020), to adjust this environment and learn intensively, and the lecturers to deliver the material concisely. E-learning has become the primary option for many institutions in Indonesia, after the spread of COVID-19 in the world, to assist the student study from home (Abidah, Hidaayatullaah, Simamora, Fehabutar, & Mutakinati, 2020).…”
Section: Introductionmentioning
confidence: 99%